2015
DOI: 10.1007/s00384-015-2286-7
|View full text |Cite
|
Sign up to set email alerts
|

Transversus abdominis plane blockade in laparoscopic colorectal surgery: a double-blind randomized clinical trial

Abstract: We conclude that TAP blockade appears to be a safe intervention but confers no specific advantage following laparoscopic colorectal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 25 publications
2
43
0
Order By: Relevance
“…Several clinical trials have reported the effect of TAP block in patients who underwent CRS [2,[9][10][11][12][13][14]; however, the results of these studies were conflicting. A clinical study conducted by Tikuisis et al [2] on 64 patients undergoing elective colonic resection for cancer reported that TAP block was effective in reducing postoperative pain and shortening the length of hospital stay.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…Several clinical trials have reported the effect of TAP block in patients who underwent CRS [2,[9][10][11][12][13][14]; however, the results of these studies were conflicting. A clinical study conducted by Tikuisis et al [2] on 64 patients undergoing elective colonic resection for cancer reported that TAP block was effective in reducing postoperative pain and shortening the length of hospital stay.…”
Section: Introductionmentioning
confidence: 86%
“…TAP block has been performed in conventional open and laparoscopic CRS in several clinical trials [2,[9][10][11][12][13][14]; however, its effect has remained controversial. Therefore, we conducted this meta-analysis based on 7 clinical trials with 511 patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations